Characterization of Electron Beam Irradiated Poly Vinyl Alcohol/Poly Ethylene Glycol Blends (Journal of Scientific Research, 2013)
Poly vinyl alcohol (PVA) and poly ethylene glycol (PEG) blends were prepared and irradiated with different electron beam irradiation doses. The influence of the irradiation dose, and PEG content on the physico-chemical properties was investigated. The data regarding gel content demonstrated that the radiation-induced crosslinking of PVA and PVA/PEG samples increased as a result of increasing irradiation dose and decreasing PEG content. The swelling volume ratio shows an opposite behavior. The XRD parameters (crystllinity percent and d-spacing values) show a decreasing behavior for PVA and PVA/PEG blends as a result of either irradiation or blending PVA matrix with PEG. The DSC data illustrate a decreasing trend in melting point, glass transition temperature, and degree of crystallinity with increasing irradiation dose or PEG content.  Keywords: Poly vinyl alcohol (PVA); Poly ethylene glycol (PEG); PVA/PEG blends; Electron beam irradiation; Swelling volume ratio; Gel content; Structural characterization  © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved  doi: http://dx.doi.org/10.3329/jsr.v6i1.13071 J. Sci. Res. 6 (1), 29-42 (2014)